Temporal changes in vegetation and mammalian communities during Oxygen Isotope Stage 3 at Sibudu Cave - Reynolds, S. C. (Southern African Humanities, 2021)
Correspondence analysis of published seed and mammalian datasets shows time-related climatic fluctuations and environmental changes in the Sibudu Cave region during Oxygen Isotope Stage 3 (OIS 3). Past vegetation and faunal communities in the Sibudu area were complex, but the macromammalian and seed species from the OIS 3 layers at Sibudu reflect broad habitat shifts which appear robust and relatively unaffected by individual species adaptations, extinctions or the actions of a single taphonomic agent. Early OIS 3 layers have ages clustering around 60 ka, and the faunal data suggest cool, dry, open woodland conditions at this time. The Late OIS 3 layers, with ages of 50 ka and 37 ka, have evidence for tree cover and forest-dwelling species. The relatively constant occurrence of equids and grazing bovids suggests that the Sibudu area was well-grassed throughout OIS 3. To cite this article: Reynolds, S. C. 2006. Temporal changes in vegetation and mammalian communities during Oxygen Isotope Stage 3 at Sibudu Cave. Southern African Humanities 18(1): 301-14.